Fecal microbiome profiles of neonatal dairy calves with varying severities of gastrointestinal disease. - Giovana S Slanzon; Benjamin J Ridenhour; Dale A Moore; William M Sischo; Lindsay M Parrish; Sophie C Trombetta; Craig S McConnel (PLoS ONE, 2022)
Gastrointestinal disease (GI) is the most common illness in pre-weaned dairy calves. Studies have associated the fecal microbiome composition with health status, but it remains unclear how the microbiome changes across different levels of GI disease and breeds. Our objective was to associate the clinical symptoms of GI disease with the fecal microbiome. Fecal samples were collected from calves (n = 167) of different breeds (Holstein, Jersey, Jersey-cross and beef-cross) from 4-21 d of age. Daily clinical evaluations assessed health status. Calves with loose or watery feces were diagnosed with diarrhea and classified as bright-sick (BS) or depressed-sick (DS) according to behavior. Calves with normal or semiformed feces and no clinical illness were classified as healthy (H). One hundred and three fecal samples were obtained from consistently healthy calves and 64 samples were from calves with diarrhea (n = 39 BS; n = 25 DS). The V3-V4 region of 16S rRNA gene was sequenced and analyzed. Differences were identified by a linear-mixed effects model with a negative binomial error. DS and Jersey calves had a higher relative abundance of Streptococcus gallolyticus relative to H Holstein calves. In addition, DS calves had a lower relative abundance of Bifidobacterium longum and an enrichment of Escherichia coli. Species of the genus Lactobacillus, such as an unclassified Lactobacillus, Lactobacillus reuteri, and Lactobacillus salivarius were enriched in calves with GI disease. Moreover, we created a model to predict GI disease based on the fecal microbiome composition. The presence of Eggerthella lenta, Bifidobacterium longum, and Collinsella aerofaciens were associated with a healthy clinical outcome. Although lactobacilli are often associated with beneficial probiotic properties, the presence of E. coli and Lactobacillus species had the highest coefficients positively associated with GI disease prediction. Our results indicate that there are differences in the fecal microbiome of calves associated with GI disease severity and breed specificities.